CHEK1 and GFPT1 as Potential Blood-Based Biomarkers for Colorectal Cancer - Habibah Faroque; Nur Soleha Aria; Nor Amira Muzilah; Hamid Ali Nagi Al-Jamal; Mohd Fadliyazid Ab. Rahim; Yasuhiro Nakamura; Hironobu Sasano; Abdullah Azmahani (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: The checkpoint kinase 1 (CHEK1) and glutamine-fructose-6-phosphate aminotransferase 1 (GFPT1) genes have been reported to have a crucial role in carcinogenesis in colorectal cancer (CRC). However, their association with the pathogenesis of CRC remains unclear. This study was conducted to study the expression of CHEK1 and GFPT1 genes in adenoma and adenocarcinoma CRC patients’ whole blood samples compared to the healthy controls.METHODS: A comparative cross‑sectional study to examine the expression of CHEK1 and GFPT1 genes were conducted in 6 colorectal adenoma and 6 colorectal adenocarcinoma patients along with 6 healthy controls. Blood samples were taken from subjects, and CHEK1 and GFPT1 genes were analyzed by using reverse transcription quantitative polymerase chain reaction (RT-qPCR). RESULTS: CHEK1 gene expression in blood samples has the highest in adenoma patients meanwhile for the GFPT1 gene expression has the highest in adenocarcinoma patients. Higher CHEK1 gene expression were also found in adenoma patients compared to healthy controls (p=0.040) and adenocarcinoma patients (p=0.025). Besides, at the 5% level of significance, the median GFPT1 gene expression was higher in colorectal adenocarcinoma patients compared to colorectal adenoma patients and healthy controls.CONCLUSION: CHEK1 and GFPT1 may function as potential regulators in adenoma and adenocarcinoma and measuring their expression might be a potential tool to determine the CRC progression and could be further explored as blood diagnostic biomarkers for CRC patients.KEYWORDS: CHEK1, GFPT1, colorectal cancer, adenoma, adenocarcinoma